COMMUNITY-BASED TOURISM PERSPECTIVE IN THE MANAGEMENT OF CULTURAL TOURISM VILLAGE “KAMPUNG MAJAPAHIT” IN BEJIJONG VILLAGE, TROWULAN DISTRICT, MOJOKERTO REGENCY - Mufidah, Nurul; Sutopo, Dhanny Septimawan (Universitas Padjadjaran, 2024)
This study aims to determine the role of “Gajah Mada” institution in the management of “Kampung Majapahit” Cultural Tourism Village based on the perspective of community-based tourism in Bejijong Village, Trowulan District, Mojokerto Regency. “Kampung Majapahit” Cultural Tourism Village is a tourist village destination that offers local wisdom in the forms of a heritage site of the Majapahit Kingdom. The management of “Kampung Majapahit” Cultural Tourism Village engages local community under an independent institution “Gajah Mada” institution. However, several attractions that are not optimally managed by the Bejijong Village community, one of which is the Majapahit house. In this qualitative research, case study approach was employed to determine the role of “Gajah Mada” institution in the management of the “Kampung Majapahit” Cultural Tourism Village within the perspective of community-based tourism. The results of this research showed that the management of “Kampung Majapahit” Cultural Tourism Village by the “Gajah Mada” institution incorporates several roles that align with a community-based tourism approach, from its structure to its principles. In general, the management was not yet optimal due to some obstacles in the management of Mahavihara Majapahit, temple and Majapahit house. It is expected that “Gajah Mada” institution implement the community-based tourism to enhance the management of the attractions.